Penapisan Fitokimia, Uji BSLT, dan Uji Antioksidan Ekstrak Metanol beberapa Spesies Papilionaceae - RATNA DJAMIL; TRIA ANELIA (JURNAL ILMU KEFARMASIAN INDONESIA, 2009)
According to literatures, many plants of Papilionaceae family such as red bean (Phaseolus vulgaris L_), green bean (Phaseolus aureus Roxb.) and soybean (Glycine soja Sieb. & Zucc.) contain flavonoid, isoflavonoid and vitamin E. They all have antioxidant activity and are potential to reduce free radical. This research was aimed to identify secondary metabolites of crude powders and extracts of red bean, green bean and soybean. The bioactivity of each extracts was evaluated with Brine Shrimp Lethality Test (B SLT) method for preliminary assesment of toxicity. It was also evaluated for antioxidant activity using 1,1 difenil-2-pikrilhidrazil (DPPH) method. The results showed that red bean, green bean and soybean contain saponin, flavonoid, steroid/triterpenoid, coumarin, and tannin. The result of BSLT showed that LC50 (Lethality Concentration 50) of red bean was 213.21 ppm; green bean 390.71 ppm; and soybean 252.75 ppm. The result of DPPH tests showed that IC50 (Inhibition Concentration 50) of red bean was 47.54 ppm; green bean 95.08 ppm; and soybean 90.43 ppm.